Thigh Rotation and the Anterior Approach to the Sciatic Nerve: A Magnetic Resonance Imaging Study. Issue 1 (1st January 2004) - Moore, Colin Scott; Sheppard, Declan; Wildsmith, John Anthony W.
Abstract : Background and Objectives: The anterior approach to the sciatic nerve block may be associated with a high failure rate because the nerve lies posterior to the lesser trochanter of the femur at the level of needle insertion. However, previous work using cadavers demonstrated that internal rotation of the leg renders the nerve more accessible to the anterior approach. Methods: Ten volunteers consented to undergo magnetic resonance imaging. Markers were placed on the surface where a needle would have been inserted for an anterior approach to the sciatic nerve. Three scans were then performed: the first with both legs in the neutral position, the second with maximal bilateral internal rotation at the hip, and the third with maximal bilateral external rotation at the hip. Results: Examination of the scans by a consultant radiologist showed that, as the thigh is rotated, the number of scans showing an unobstructed needle passage from the skin marker to the sciatic nerve rate increased from 5% in external rotation to 85% in internal rotation. The number of times the needle path passed through femoral neurovascular bundle also fell from 55% in external rotation to 15% in internal rotation. Conclusions: The results confirm that, as the thigh is moved from an externally to an internally rotated position, the sciatic nerve becomes more accessible by the anterior approach at the level of the lesser trochanter, and the risk of femoral artery or nerve puncture is reduced but not eliminated.